One-Pot Synthesis of Quinazolinones from Anthranilamides and Aldehydes via p-Toluenesulfonic Acid Catalyzed Cyclocondensation and Phenyliodine Diacetate Mediated Oxidative Dehydrogenation - Cheng, Ran; Guo, Tianjian; Zhang-Negrerie, Daisy; Du, Yunfei; Zhao, Kang (Synthesis, 2013)
A variety of 4(3H)-quinazolinones are synthesized conveniently in one pot from 2-aminobenzamides and aldehydes, via cyclization catalyzed by p-toluenesulfonic acid followed by oxidative dehydrogenation mediated by the hypervalent iodine compound phenyliodine diacetate [PhI(OAc)2, PIDA]. Highlights of the described method include the first synthesis of quinazolinones bearing an N-alkoxy substituent, a new application of phenyliodine diacetate as an efficient dehydrogenative oxidant, and mild reaction conditions.
Keywords: quinazolinones; cyclocondensation; dehydrogenation; phenyliodine diacetate; one-pot synthesis